PEMAKNAAN DEKONSTRUKSI KONSEP PEREMPUAN IDEAL DALAM FILM PENGABDI SETAN (2017) - Wawat Rahwati; Cut Novita Srikandi; Nina Alia Ariefa Alia Ariefa; Bustanuddin Lubis (LINGUA : JURNAL ILMIAH, 2020)
Abstract This article aims to reveal the deconstruction meaning of the ideal women concept in film Pengabdi Setan through the characters of Mother and Grandmother. Jacques Derrida's concept is used in this study to see how text can be interpreted not only in a single meaning but also another meaning, as a main characteristic of deconstruction is to reveal the meanings that are marginalized, ignored, and hidden. We use deconstruction reading methodology to reveal the hidden meanings in the film Pengabdi Setan (2017). By deconstructing a concept of women which presented by mother and grandmother figures, we found several results were obtained such as the concept of ideal women that admitted in our society still shackles women so that if a woman does not conform to the ideal concept prevailing in society, then what will happen is a catastrophe. In Indonesian society which is still strongly conduct to patriarchal values, women are often alienated and negatively stigmatized if they cannot bear children. Reproductive tasks that are carried out by women are shown and regulated according to the wishes of society, for example when she should get pregnant and how many children will be conceived and born. The mother has to take care of her husband, children, and household. Society has constructed women as ideal figures who serve their husbands and work fully in the domestic area, such as taking care of kitchens, wells, and mattresses. Abstrak Penelitian ini bertujuan untuk mengungkap pemaknaan dekonstruksi konsep perempuan ideal dalam film Pengabdi Setan melalui tokoh ibu dan nenek. Konsep Jacques Derrida digunakan dalam penelitian ini untuk melihat bagaimana teks mampu dimaknai tidak hanya dalam pemaknaan tunggal karena inti dari dekonstruksi adalah menyingkap makna-makna yang dipinggirkan, diabaikan, dan disembunyikan. Penulis menggunakan metodologi pembacaan dekonstruksi untuk menyingkap makna yang tersembunyi dalam film Pengabdi Setan (2017). Dengan mendekonstruksi konsep perempuan yang dihadirkan melalui tokoh ibu dan nenek, didapat beberapa hasil penelitian, di antaranya konsep perempuan ideal yang berkembang di masyarakat masih membelenggu perempuan sehingga jika perempuan tidak sesuai dengan konsep ideal yang berlaku di masyarakat, yang terjadi adalah malapetaka. Dalam masyarakat Indonesia yang masih sarat dengan nilai patriarki, perempuan sering diasingkan dan distigmakan negatif jika ia tidak dapat melahirkan anak. Tugas reproduksi yang dijalankan perempuan diperlihatkan dan diatur sesuai dengan kehendak masyarakat, misalnya kapan ia harus hamil dan berapa banyak anak yang akan dikandung dan dilahirkan. Ibu harus mengurus suami, anak-anak, dan rumah tangganya. Masyarakat telah mengkonstruksi perempuan sebagai sosok yang ideal, yang mengabdi pada suami dan bekerja sepenuhnya di wilayah domestik, seperti mengurus dapur, sumur, dan kasur.